ENTREPRENEUR INTENTION AMONG COLLEGE STUDENT IN RIAU PROVINCE - Adrian Irnanda Pratama; Novira Sartika (Politeknik Negeri Bengkalis, 2018)
This study aim to examine which factors can influence entrepreneurship intention among college student in Riau Province from several factors by previous researches scholars: personality characteristic factors, entrepreneurial competencies factors, and environmental factor. This study applies correlation and regression analysis to test on the sample of 105 college student by using electronic questionnaire. This research shows that the correlation coefficient all independent variable to the dependent variable is significant. Moreover, this study indicate that determinants of entrepreneurial intention (personality characteristic, entrepreneurial competencies, and environmental) were have significant impact on the entrepreneurial intention among college student in Riau Province Indonesia.